Efektivitas Program Pemberdayaan Perempuan Miskin pada Koperasi Baytul Ikhtiar (BAIK) Bogor - Faridatuz Zakiyah (UIN Raden Mas Said Surakarta, 2018)
Giving roles, opportunities and means for women to be empowered in all things, including in the economy is one of the efforts to alleviate poverty. The poor women's empowerment program conducted by the Koperasi Baytul Ikhtiar (BAIK) has helped many poor women in Bogor. This is in line with the Koperasi’s goal of building community and building a national economic order by empowering and prospering members of the cooperative which consists of poor women. This study aims to determine the effectiveness of poor women's empowerment programs that have been carried out by Koperasi Baytul Ikhtiar Bogor. Effectiveness is analyzed by looking at the effect of participation on effectiveness which is moderated by the performance of the facilitator. The study was conducted in Tamansari, West Bogor. This quantitative research was carried out by distributing 114 questionnaires, but only 62 were analyzed because others were missing. Data analysis using Partial Least Square with smartPLS 2.0 software. The results of the study indicate that participation which consists of the planning stage does not directly or indirectly affect effectiveness. The participation of both stages of the implementation has a direct effect and does not have an indirect effect through the performance of the facilitator on effectiveness. While the third participation, the evaluation phase does not have a direct effect but affects the effectiveness through the performance of the facilitator. For participation which consists of the planning stage, the implementation phase and evaluation phase indirectly influence the effectiveness through the performance of the facilitator with the highest score among others. This shows that the performance of Koperasi Baytul Ikhtiar Bogor employees has a strong influence on the end result or effectiveness of the empowerment program for poor women members of the Koperasi Baytul Ikhtiar (BAIK) Bogor.